STRATEGIES APPLIED IN ENGLISH INTO INDONESIAN TRANSLATION OF PRISON SLANG WORDS IN “THE SHAWSHANK REDEMPTION” MOVIE SUBTITLING - Pratama, Agus Darma Yoga; Artawa, Ketut; Putra Yadnya, Ida Bagus; Sri Satyawati, Made (e-Journal of Linguistics; 2016: Vol. 10 No. 2 July)
The rapid advancement of technology and the presence of Internet have a tremendous impact on translation industry. There are various types of translation domains, one among which is subtitling. This study deals with: 1) strategies applied in the English into Indonesian translation of prison slang words in “The Shawshank Redemption” movie subtitling using the theory on translation strategies proposed by Gottlieb (1992); and 2) the most frequent strategy and type of translation (literal to idiomatic translation) of the prison slang words using the theory on translation typologies proposed by Larson (1984). There are 12 prison slang words found in the movie and used as data in this study. Some of the prison slang words appear more than one time, but there are only 24 sentences and phrases containing prison slang words used as data in this study. Among the data, the most frequent translation strategies used are the ‘transfer’ strategy, followed by three occurrences of ‘condensation’ strategy and two deletions. Most of the translations are idiomatic translations. Some are literal translations yet they do not really distort the meaning intended in the prison slang words concerned. In conclusion, translating prison slang words is not an easy job. The subtitler must do adequate research to understand which meaning is intended by the author with the help of visual images, gestures and tones used by the actors in the movie.
Keywords: Subtitling, Translation Strategies, Prison Slang, Transfer, Condensation, Deletion, Idiomatic, Literal